The Emergence of State Sphere in Social Media: A Political Balkanization in Malaysia - Mohamed@Bakar, Badrul Azmier; Yusoff, Moharnrnad Agus; Mohd. Zain, Zawiyah; Efendi, Dori (Khalsa Publications, 2014)
Social media has phenomenally replaced the traditional media. Blogs have transformed news reporting; YouTube has reinvented talent sourcing; and “the trinity” (Facebook, Twitter, and YouTube) have revolutionary changed the rules of the game of regime change. Enabling commoners to be producers and its interactiveness are the two most important characteristics that grant the ordinary citizens to be extra-ordinary. From Tinseltown to Alexandria, the roles of social media has been unstoppably growing. The world political events in the recent times, particularly the Arab Spring have shown a strong correlation between social media and democratization. Malaysia’s political experience in recent years, in particular the 12th General Election (GE-12) in 2008 is comparable to the Arab Spring in view of the alluring role of social media and its gladiatorial impacts in politics. The failure of Barisan Nasional (BN or National Front, the only ruling party since independence) to retain its customary two-third majority in GE-12 is a proof of people’s growing desire to enjoy democracy that among others offer free and fair elections, good-governance, and social justice which are dissimilar to existing communalism and strong government. At a glance, GE-13 in 2013 produced similar results as GE-12 which displayed fortification of democracy among citizens. In contrast, further analyses toward the details of GE-13 surfaced the revival of communalism and autoritarinism which have shown signs of decay in GE-12. Thus, this article explores the conflictual roles of social media which (has been functioning as an ideal public sphere) when the ruling party together with the state machinery invade the sphere of social media to satisfy their political agenda. This investigation showcases the anarchic sphere in social media is not only capable in catalyzing democratization, but also undermining democracy by propagating political Balkanization that propels disjointed feelings among multi-racial citizens